Autoimmune pancreatitis and ulcerative colitis: A clinical challenge of a true association - Barreiro,Pedro (2013)
Autoimmune pancreatitis is emerging as a well-defined clinical entity, yet its diagnosis and therapeutic approach still constitute a clinical challenge. Its association to other autoimmune diseases, namely ulcerative colitis, is known although the exact relationship between the two entities is not completely clarified. We present the case of a patient who developed obstructive jaundice with later onset of blood-stained diarrhea, leading to a final diagnosis of autoimmune pancreatitis and ulcerative colitis. We make a brief revision of autoimmune pancreatitis, its relationship with ulcerative colitis and therapeutic approaches of the same, namely the eventual necessity of immunosuppressive therapy.